OPTIMALISASI LIMBAH CAIR KELAPA SAWIT SEBAGAI ENERGI TERBARUKAN DAN BERKELANJUTAN: Studi Kasus di Pabrik Kelapa Sawit PT Tunas Baru Lampung - Suksmanantyo; Wahdianto, Rahmad Waris; Wardana, Hery Setia; Meganesia, Lukiswara; Suheriyanto; Wahyudi, Brian Fitri (Institut Teknologi Sawit Indonesia (ITSI), 2025)
Palm Oil Mill Effluent (POME) is a major by product of the palm oil industry, characterized by high organic content (COD 40,000 - 100,000 mg/L) and significant environmental risk if untrated. This study aims to Optimize POME conversion into biogasthrough anaerobic digestion, focusing on technical parameters (COD, pH, temperature) at PT Tunas Baru Lampung. Using a quantitative approach, data were collected over 12 months and analyzed via multiple linear regression. Results indicate COD as the dominant factor (β = 0.866, p=0.000), with optimal biogas production at pH 6.8 - 7.4 and mesophilic temperatures (30–40°C). The estimated electricity potential reached 54.62 MW/month, reducing CO₂ emissions by 21,533 tons/year. Challenges include infrastructure limitations and regulatory gaps. Recommendations include adopting advanced digester technologies, policy incentives, and further industrial-scale research. This study contributes to green manufacturing by aligning waste management with renewable energy goals and circular economy principles